Hydrogen Peroxide Detection Using Reversible Luminescent CeO2-x and CeO2-x:Eu3+ Nanocrystals - Maksimchuk, P.; Neuhodov, Y.; Hubenko, K.; Onishchenko, A.; Kavok, N.; Dudetskaya, G.; Kot, Y.; Yefimova, S.; Seminko, V. (Institute of Physics of the National Academy of Sciences of Ukraine, Taras Shevchenko National University of Kyiv Ukrainian, Physical Society, 2024)
Hydrogen peroxide (HP) is a prevalent industrial chemical used extensively for bleaching, cleaning, and disinfection. In biological systems, HP acts as a crucial signaling molecule and is involved in various enzymatic processes as a substrate or byproduct, such as those involving catalase, superoxide dismutase, and numerous oxidases and peroxidases [1, 2]. Thus, precise HP sensing is vital for monitoring its concentration in both industrial and biological contexts
Keywords: hydrogen peroxide; biological systems